"What Guarantees Do We Have?" Legal Tolls and Persistent Impunity for Feminicide in Guatemala. (December 2016) - Walsh, Shannon Drysdale; Menjívar, Cecilia
ABSTRACT: Guatemala has one of the highest levels of killings of women and impunity for violence against women in the world. Despite laws created to protect women, Guatemala, like other countries, generally fails at implementation. This article examines justice system obstacles in contemporary Guatemala to processing cases of feminicide—killings of women because they are women in a context of impunity—comparing two recent feminicide cases. It argues that the sociopolitical context in Guatemala, including structural violence, widespread poverty, inequality, corruption, and normalization of gender violence against women, generates penalties, or "legal tolls, " that are imposed on victims' families and contribute to impunity through undermining victims' attempts to navigate the justice system. The analysis focuses on the tolls of fear and time: the need to overcome fear of retaliation and the extraordinary time and effort it takes to do so in a corrupt and broken system.